Composition and structure of a lowland forest in the core zone of the Bukit Duabelas National Park, Jambi, Indonesia - Azwar Anas; Kuswata Kartawinata; Nisyawati Nisyawati (Universitas Pakuan, 2021)
The objective of the study was to obtain data on composition and structure of the forest in the midsection of the Bukit Duabelas National Park core zone, designed to complement the existing data and provide new information potentials for the management of the park core zone. The study was carried out in October-November 2012. Observations were made on plots of one hectare (100 m x 100 m), which was divided into 100 subplot, measuring 10 m x 10 m each. Enumeration of tree species with diameters â‰¥ 10 cm revealed that as many as 540 individuals were recorded, consisting of 89 species and 36 families, with a total basal area of 30.837 m2 and only three species of Dipterocarpaceae were registered. The forest had a low diversity as indicated by low species richness, much lower than in the undisturbed lowland primary forests in the Batang Gadis National Park in North Sumatra, where similarity was very low (5.9 %). The forest in the plot was designated as the Dacryodes rostrata- Shorea leprosula Association, named after two species with highest importance values, thus the dominant. The structure and species composition pointed to the regenerating forest after heavy disturbances. The forest has been undergoing slow natural succession, leading to the formation of the forest similar to the original climax forest. Natural recovery through succession could be enhanced and assisted by means of ecological restoration, through planting of tree species characteristics of forests in Jambi, including species of Dipterocapaceae, useful species having values to maintain the livelihood of the indigenous native tribe Suku Anak Dalam and rare, endemic other species having high conservation values. Tujuan studi ini adalah untuk memperoleh data tentang komposisi dan struktur hutan di bagian tengah zona inti Taman Nasional Bukit Duabelas. Studi dirancang untuk melengkapi data yang telah ada dan untuk menyajikan informasi baru yang berpotensi untuk digunakan dalam pengelolaan zona inti taman nasional. Penelitian dilaksanakan pada bulan Oktober-November 2012 dalam petak seluas satu hektare (100 m x 100 m), yang dibagi menjadi 100 anak-petak dengan ukuran masing-masing 10 m x 10 m. Pencacahan pohon dengan diameter â‰¥ 10 cm menghasilkan 540 batang, yang terdiri atas 89 jenis dan 36 suku, dengan luas bidang dasar total 30.837 m2 dan hanya tercatat tiga jenis Dipterocarpaceae. Keanekaragaman jenis hutan rendah, seperti ditunjukan oleh rendahnya kekayaan jenis, jauh lebih rendah dibandingkan dengan hutan primer yang tidak terganggu di Taman Nasional Batang Gadis di Sumatra Utara, yang mempunyai kesamaan hanya 5,9 % dengan Taman Nasional Bukit Duabelas. Berdasarkan dua jenis dominan dengan nilai kepentingan tinggi, komunitas pohon dalam petak dinamakan Asosiasi Dacryodes rostrata- Shorea leprosula. Struktur dan komposisi jenis menunjukan status hutan sebagai hutan yang sedang beregenerasi setelah mengalami gangguan. Hutan sedang mengalami suksesi alami yang lambat menuju ke pembentukan hutan yang serupa dengan hutan klimaks aslinya. Pemulihan alami melalui suksesi dapat dipercepat dan dibantu dengan restorasi ekologi melalui penanaman jenis-jenis khas hutan alami Jambi, termasuk Dipterocapaceae, jenis-jenis bermanfaat dan mempunyai nilai untuk keberlanjutan kehidupan dan kesejahteraan masyarakat asli Suku Anak Dalam dan jenis-jenis langka, endemik dan jenis lain yang mempunyai nilai konservasi tinggi.